Futures Studies of the Integrated Ecosystem of Sports Brands with an Emphasis on Technological Transformations - Karimzadeh, Mohammad; Hosseini Semnani, Akram Sadat; Saffari , Leila (Journal of Foresight and Health Governance, 2025)
This study aims to explore the future configuration of the integrated ecosystem of sports brands with a particular focus on emerging technological transformations and their strategic implications. The research employed a qualitative exploratory futures-studies design drawing on expert-driven foresight methodologies. Participants were selected based on purposive and criterion sampling, including sports branding specialists, digital transformation experts, technology innovators, and academic researchers with significant experience in sports ecosystems. Data were collected through semi-structured in-depth interviews, expert panel discussions, and systematic documentary analysis of global technological and market reports. The analytic process involved iterative thematic coding, structural analysis through the MICMAC method to map influence–dependence relationships among key variables, and intuitive-logics scenario building to construct plausible future trajectories. Cross-validation among interview insights, panel deliberations, and documentary evidence ensured conceptual coherence and analytical rigor. Analyses revealed that the future of sports brand ecosystems will be predominantly shaped by technological convergence, including AI-driven personalization, IoT-enabled fan engagement, immersive AR/VR experiences, and platform-based value creation. MICMAC results showed strong influence pathways among technological, economic, and consumer-behavior variables, indicating that digital infrastructures will become the core enablers of brand competitiveness. Scenario building produced four plausible futures driven by uncertainties associated with technology adoption, data governance, and platform dominance. Across scenarios, strategic agility, consumer co-creation, sustainability pressures, and globalized digital commerce emerged as decisive factors shaping long-term ecosystem configurations. The study concludes that sports brands are transitioning from traditional linear branding models to interconnected digital ecosystems driven by technological innovation, evolving consumer expectations, and expanding global platforms.